Review of Switched Beamforming Networks for Scannable Antenna Application towards Fifth Generation (5G) Technology - Mohd Suhaimi, Nazleen Syahira; Mahyuddin, Nor Muzlifah (International Journal of Integrated Engineering, 2020)
The next generation wireless network (5G) addresses the evolution beyond mobile internet to massive Internet-of-Things (IoT) which will take off from 2019/2020 onwards. The essential design features in 5G wireless network system are massive multiple-input and multiple-output (MIMO) and steerable antenna array. The higher capacity, lower power transmission and larger system coverage offered by upcoming 5G technology can be realized using switched-beam antenna such as Butler matrix, Rotman lens, Blass matrix and Nolen matrix. Review of their design features and performance results will be compared in this article. Butler matrix can be the best approach owing to low complexity, orthogonal beams and less components utilization.